Unique guiding catheter induction technique using aspiration catheter and Amplatz super-stiff guidewire for thrombectomy - Eisuke Tsukagoshi; Hiroki Sato; Shinya Kohyama (Interdisciplinary Neurosurgery, 2023)
Placement of guiding catheters (GCs) in older patients who undergo thrombectomy is often difficult owing to age-related atherosclerotic changes. Herein, we propose a unique technique of balloon guide catheter (BGC) implantation for thrombectomy termed the AC-Amplatz wire method (Aspiration Catheter – Amplatz Super-Stiff Guidewire method). Using the AC-Amplatz wire method, AC was first guided to the C5 portion of the internal carotid artery followed by passing this Amplatz wire through it. Using this novel method, flow control with BGC and good recanalization were achieved. The AC-Amplatz wire method was very effective in GC placement in patients with torturous and atherosclerotic vasculature.